Pharmacologic Manipulation of Emergence after Adenotonsillectomy for Pediatric Obstructive Sleep Apnea: A Prospective Controlled Study. (23rd August 2013) - Isaiah, Amal; Stein, Rebecca; Shapiro, Scott; Bellefleur, Monique; Pereira, Kevin D.
Abstract : Objectives: 1) Elucidate the factors affecting emergence from anesthesia after adenotonsillectomy for obstructive sleep apnea (OSA) in children. 2) Highlight the advantages of a standardized anesthetic protocol in controlling peri‐operative events. Methods: A non‐randomized, prospective, observational study (n = 64) was designed to examine the relationship between the severity of OSA, as determined by apnea‐hypopnea index (AHI) and oxygen saturation (SpO2) nadir, and indices of recovery, including time to 1) emergence after surgery, 2) extubation following emergence, and 3) discharge from the post‐anesthesia care unit. A standardized anesthetic protocol was used in all patients using doses of opioids that inversely correlated with OSA severity. Results: A paradoxical yet significant reduction in recovery time was observed among patients with severe OSA following surgery; this reflected in quicker emergence, accelerated extubation, and shortened postanesthesia care unit discharge times (analysis of variance, Tukey‐Kramer post‐hoc tests, P < 0.001) besides a reduction in adverse events. In addition, the relationship between polysomnography (PSG)‐derived AHI and SpO2 nadir varied inversely with each of the recovery indices, as determined by a linear regression analysis (t‐tests, P <0.001). Conclusions: Emergence from anesthesia after adenotonsillectomy can be controlled by a standardized anesthesia protocol using different combinations of sedation and analgesia. The severity of sleep apnea and hypoxemia do not independently appear to play a significant role in recovery from anesthesia. By using a standardized anesthetic protocol with diminishing doses of opioids with increasing severity of OSA, our results indicate a striking departure from previously observed findings relating to post‐procedural respiratory complications following adenotonsillectomy.